Analisis Kualitas Pelayanan Publik pada Kantor Camat Marusu Kabupaten Maros - Arni Arni (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study aims to analyze the quality of public services at the Marusu Sub-district Office in Maros Regency. The research uses a qualitative method with data collection through interviews and observations. The informants consisted of the Sub-district Head and staff members at the sub-district office. The results show that, overall, the quality of service at the Marusu Sub-district Office demonstrates a strong commitment to meeting community needs. The services provided are perceived as good, particularly in terms of responsiveness and professionalism of the officers. However, there are several areas that need improvement, such as inadequate facilities, suboptimal infrastructure, and the need to strengthen human resources to deliver more efficient and effective services. Overall, despite some shortcomings, the quality of service at the Marusu Sub-district Office meets the service standards expected by the public, with potential for further improvement.